Visibility, resilience, vulnerability in young migrants. (September 2019) - Bradby, Hannah; Liabo, Kristin; Ingold, Anne; Roberts, Helen
Young unaccompanied asylum seekers have been portrayed as vulnerable, resilient or both. Those granted residency in Europe are offered support by health and social care systems, but once they leave the care system to make independent lives, what part can these services play? Our review of research with migrants who have been in care in Sweden and the United Kingdom found evidence of unmet need, but little research describing their own views of services. The limited published evidence, supplemented by interviews with care leavers in a UK inner city, suggests that in defining health needs, young people emphasise housing, education, employment and friendship over clinical or preventative services. Some felt well supported while others described feeling vulnerable, anxious, angry or sad. These experiences, if linked with the insensitivity of even one professional, could lower young people's expectations of healthcare to the extent that they avoided contact with service providers. In supporting young migrants' resilience to meet everyday challenges, friendly support from peers, carers and professionals was important. They needed determined advocacy at key moments. The different challenges for the Swedish and UK health and welfare systems along with the resilience/vulnerability trajectory are described.